Assessing the Impact of Flood Experience on Household Livelihood in Selected Communities Within the Greater Accra Metropolitan Area (Gama) - Tungbani, B. (University of Ghana, 2021)
Flood experience and household livelihood disruption remain a global challenge. This is most severe in developing countries which still records very high cases of flood disasters. The study examined the relationship between flood experience and household livelihood outcomes in selected communities within the seven districts forming the Greater Accra Metropolitan Area (GAMA). Flood experience in the study was measured based on households' frequency of floods experienced occasionally, yearly, and seasonally. Household livelihood outcome was measured by a composite index score as livelihood disrupted. Bivariate and multivariate analyses were used to examine the relationship between flood experience and household livelihood outcomes. The 2017 Cities and Climate Change survey is the main data source of the study. The study used a sub-sample of 823 households that experience floods in the study area. A majority (78%) of the households were found to be experiencing flooding yearly and seasonally which indicates that floods experience among the study population was prevalent. Results from the analysis indicate that; flood experience, employment status, district of residence, the community of location, and household level of adaptation were statistically significant predictors variables on household livelihood disruption. However, educational attainment, wealth group, age, sex, marital status, household size, tenancy agreement, and the community level adaption outcome were not significant predictors of household livelihood disruption. The study, therefore, concludes that the entire study area is vulnerable to the occurrence of floods and recommends that interventions should be made by the individual, community, and government levels in mitigating flood disasters.
MA. Population Studies
Keywords: Floods; Livelihood; Adaptation; Vulnerability; Mitigation